EFEKTIVITAS ETHYL METHANE SULFONATE (EMS) TERHADAP PEMBENTUKAN TANAMAN WORTEL (Daucus carota L.) MANDUL JANTAN - Gungun Wiguna; Rd. Prasodjo Prasodjo; Uun Sumpena (Universitas Wahid Hasyim, 2011)
The study was conducted at Indonesian Vegetable Research Institute in March to December 2009 with an altitude of 1250 masl. The objective of study was to determine the effectiveness of EMS in producing carrots male sterile. The experiment was arranged in Complitely Randomized Block Design with two factors and three replication. The results indicate that the local carrot cultivars have the survival to maturity better than hybrid varieties. The highest percentage of living plants showed by carrot cultivar origin Cipanas (73.21%). The percentage of live plants is affected by the EMS treatment only until the age of 60 HST. Increased concentrations of EMS resulted in decreased percentage of live plants. Increased concentrations of EMS also tends to reduce the weight of thousand grains carrot seed produced from the M1 generation. Visual appearance of pollen on all EMS treated the same as the control, that is pithy and bright yellow. Treatment of various EMS concentrations level provided the individual has not been effective in producing carrots male sterile. Key words: carrot, male sterile, EMS.